2006
DOI: 10.1109/tnano.2005.861402
|View full text |Cite
|
Sign up to set email alerts
|

Threshold error penalty for fault-tolerant quantum computation with nearest neighbor communication

Abstract: Abstract-The error threshold for fault-tolerant quantum computation with concatenated encoding of qubits is penalized by internal communication overhead. Many quantum computation proposals rely on nearest neighbor communication, which requires excess gate operations. For a qubit stripe with a width of + 1 physical qubits implementing levels of concatenation, we find that the error threshold of 2.1 10 5 without any communication burden is reduced to 1.2 10 7 when gate errors are the dominant source of error. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…The main alternative to topological codes is code concatenation, where codes are nested inside of codes [62], which is the approach taken in this proposal. There have been encouraging results in thresholds with concatenation [6,55,76,140], as well as investigations into two-dimensional and LNN architectures [68][69][70]75,81,82,138,141]. Knill demonstrated that small quantum codes (such as the four-qubit code studied here) can be effective when concatenated [6].…”
Section: A Background On Error Correction In Constrained Geometriesmentioning
confidence: 88%
See 1 more Smart Citation
“…The main alternative to topological codes is code concatenation, where codes are nested inside of codes [62], which is the approach taken in this proposal. There have been encouraging results in thresholds with concatenation [6,55,76,140], as well as investigations into two-dimensional and LNN architectures [68][69][70]75,81,82,138,141]. Knill demonstrated that small quantum codes (such as the four-qubit code studied here) can be effective when concatenated [6].…”
Section: A Background On Error Correction In Constrained Geometriesmentioning
confidence: 88%
“…Our error correction schemes are simple two-, three-, and four-qubit quantum codes that have been mapped to the linear array of qubits [68][69][70] because alternatives like the surface code [8,[71][72][73] and Bacon-Shor code [74][75][76] are not effective in a linear geometry [77][78][79]. Our logical qubit is supported with simulations of error correction that can be compared with other proposals [13,58,[69][70][71]73,75,76,[80][81][82][83][84][85][86][87]. Finally, we are careful to note that a purely linear architecture is not extensible to an arbitrary number of qubits, for the simple reason that a single defective qubit anywhere results in two noninteracting arrays.…”
Section: Introductionmentioning
confidence: 99%
“…The first and most important class of these is the Calderbank-Shor-Steane (CSS) codes [Calderbank and Shor 1996;Shor 1996;Steane 1996;Preskill 1998b]. The theory and practice (including both experimental demonstrations [Chiaverini et al 2004;Pittman et al 2005;Roos et al 2004] and system design [Svore et al 2005;Steane 2002;Copsey et al 2003;Burkard et al 1999;Devitt et al 2004;Metodiev et al 2003;Szkopek et al 2004]) of QEC and FT operation are vast; we will not cover them in any depth here. Nevertheless, a basic understanding of the pressures that QEC and FT place on architecture is critical.…”
Section: Error Managementmentioning
confidence: 99%
“…Unfortunately, this syndrome calculation and measurement process may also introduce errors. Technologies that support nearest-neighbor-only interactions require swapping of qubits in order to calculate the error syndrome, with the swap gates possibly introducing errors themselves, making the threshold requirements for effective error correction more stringent; in some studies, as much as 175 times worse [Svore et al Aharonov and Ben-Or 1999;Szkopek et al 2004]. Applying two-qubit gates can result in the propagation of an error from one qubit to another, even from the target of the gate to its control.…”
Section: Error Managementmentioning
confidence: 99%
“…for a local architecture [5,6] to 10 −5 − 10 −2 for non-local gates [4,7]. With the present technology these rates are hardly achievable by any real device.…”
Section: Introductionmentioning
confidence: 97%